Fresno County Bar Association's 18th Annual Judges Dinner at Crossland's Barn - Watkins, Howard::::::::: (1987)
Judge James Ardaiz and Samuel Palmer III; Larry O'Neill and Melinda Vaughn on left; Donald Fischbach in background